Perlindungan Hukum Jasa Keuangan Fintech Dalam Perkembangan Ekonomi Di Indonesia Pada Era Indusri 4.0 - Mey Shinta Nur Azizah; Ayub Torry Satriyo Kusumo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Fintech-based financial services sector in Indonesia shows developments that are in line with regional and global sector dynamics. This development plays an important role in accelerating national economic growth, where the financial services sector functions optimally to maintain the smooth running of the financial system. This system is the foundation for sustainable development, supports community financial independence, and improves the distribution of development. This study uses a normative juridical approach with descriptive analysis. The data was analyzed qualitatively and juridically. The research results show that regulations in the financial services sector are developing rapidly due to demands from regional and global changes. One of the main challenges faced is the ASEAN Banking Integration Framework (ABIF). Legal developments in this sector can be seen in regulatory changes in institutions, services, products, and dispute resolution. Legal reform is still needed to provide a strong legal basis for the financial services sector, especially in civil and banking law. This reform aims to adapt regulations to the latest developments and ensure the stability and reliability of the financial services sector in the future.